2018
DOI: 10.1016/j.jshs.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fitness level on cardiac autonomic regulation, IL-6, total antioxidant capacity, and muscle damage responses to a single bout of high-intensity interval training

Abstract: PurposeThe aim of this study was to investigate the influence of the cardiorespiratory fitness level on the response to high-intensity interval training (HIIT) with an individually adjusted running speed of the same relative intensity. The evaluation focused on acute cardiorespiratory response, postexercise cardiac autonomic modulation (heart rate variability (HRV)) and biochemical markers of inflammation, oxidative stress, and muscle damage.MethodsThirty participants were divided into 3 subgroups: well traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
2
25
0
1
Order By: Relevance
“…This phenomenon might result from the mobilization of low-molecular-weight antioxidants (such as reduced glutathione and vitamin C) from other tissues, and their release into circulation in order to counterbalance the enhanced synthesis of free radicals [ 22 , 23 ]. In line with these findings, an increase in TAC may be a simple marker of free radical overproduction [ 24 ]. However, the lack of measurement of nonenzymatic antioxidants such as reduced glutathione, vitamin C, or others in the present study may be considered a limitation and further research is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 86%
“…This phenomenon might result from the mobilization of low-molecular-weight antioxidants (such as reduced glutathione and vitamin C) from other tissues, and their release into circulation in order to counterbalance the enhanced synthesis of free radicals [ 22 , 23 ]. In line with these findings, an increase in TAC may be a simple marker of free radical overproduction [ 24 ]. However, the lack of measurement of nonenzymatic antioxidants such as reduced glutathione, vitamin C, or others in the present study may be considered a limitation and further research is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have shown that sarcopenia is one of the risk factors for chronic cardiovascular disease. Patients with heart failure (HF) often suffer from sarcopenia at the same time, and improving muscle loss in HF patients is an effective treatment strategy (Chin et al, 2013;Loncar et al, 2013;Cipryan, 2018). It was reported that the muscle mass, strength and function of the leg muscles of diabetic patients are rapidly decreasing compared with those with normal blood glucose, and it has been proposed that the development of personalized functional exercises for the elderly with diabetes is of great significance in preventing and treating sarcopenia (Leenders et al, 2013;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The wide variation in intensity that occurs in sprints during soccer matches might be the reason for the high correlation found by Thorpe et al ( Thorpe and Sunderland, 2012 ). Inter-individual variability, intensity, session volume, type of exercise evaluated, and the level of sports activity can influence the CK change in a given exercise ( Baird et al, 2012 ; Cipryan, 2018 ).…”
Section: Discussionmentioning
confidence: 99%